Reduction of heterocyclic amine formation in beef by surface application of spices - Brensing, Tess (Kansas State University, 2011)
Heterocyclic amines (HCAs) are cancer causing compounds formed during the cooking of meat. Previous studies show that incorporating antioxidant spices into meat as well as marinating meat with antioxidant spices reduces formation of HCAs. The purpose of this study was to determine if commercially available spices applied to the surface of meat could effectively reduce HCA formation. Two commercially available spice blends and one blend of spices with known quantities of antioxidant spices were sprinkled onto the surface of beef just prior to pan-frying. The quantities of spices used were based on the amounts customarily consumed in typical Western cooking. The results of direct application were then compared to marinating with the same types and amounts of spices. The antioxidant potential of the spices was analyzed using DPPH and total phenolics methods. Results indicated that the spices would be effective antioxidants. Low recovery rates and problems during the extraction process made results inconclusive, but suggest that further research may find that applying spices directly to the surface of meat in consumer acceptable quantities may be as effective as marinating at reducing the formation of HCAs.
Keywords: Heterocyclic amine; Beef; Spices; Surface application; Food Science (0359)